ANTIDEPRESSANT EFFECT OF ETHANOLIC EXTRACT OF MIMOSA PUDICA COMPARED WITH IMIPRAMINE IN MICE MODELS - DSOUZA, FLOYD VERNON; M, JAYARAJ; DSOUZA, HALMOND MELROYD (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Background: Depression was considered as mental illness worldwide. Various symptoms observed with depression are loss of interest, sad mood, disturbed sleep, low energy, and loss of appetite. Mimosa pudica is a traditional medicine having various medicinal properties. Imipramine is a tricyclic antidepressant drug used in depression. This study is to evaluate the antidepressant activity of ethanolic extract of M. pudica leaves and imipramine in mice models. Methods: Swiss albino mice weighing 20–25 g of either sex was involved in study. In each study, the animals were divided into five groups (n=6). Drug was administered i.p. and the antidepressant activity was performed using tail suspension test (TST) and forced swim test (FST) in Group 1 – control group, Group 2 received imipramine (10 mg/kg), and Groups 3, 4, and 5 received M. pudica extract of (4, 6, 8 mg/kg). Results: The study shows the significant reduction in immobility in acute and chronic study of TST and FST with M. pudica extract of (6 mg/kg) and imipramine when compared with control and other extracts of M. pudica (4 mg/kg and 8 mg/kg) Conclusions: The study concluded that the ethanolic extract of M. pudica has significant antidepressant activity and can be, further, considered for the treatment of depression.